Changing Working Environments in Philosophy: Reflections from a Case Study - McConwell, Alison; Bogacz, Magdalena; Brecevic, Char; Haber, Matthew; Wu, Jingyi; Roe, Sarah (Philosophy of Science, 2025)
Abstract There is an “underrepresentation problem” in philosophy departments and journals. Empirical data suggest that while we have seen some improvements since the 1990s, the rate of change has slowed down. Some posit that philosophy has disciplinary norms making it uniquely resistant to change. We present results from an empirical case study of a philosophy department that achieved and maintained male-female gender parity among its faculty as early as 2014. Our analysis extends beyond matters of gender parity because that is only one, albeit important, dimension of inclusion. We build from the study to reflect on strategies that may catalyze change.
Keywords: Computer science; Epistemology; Philosophy; Sociology; dept.his; peer-reviewed